Yoga for Chronic Neck Pain: A 12‐Month Follow‐Up. Issue 4 (6th February 2013) - Cramer, Holger; Lauche, Romy; Hohmann, Claudia; Langhorst, Jost; Dobos, Gustav
Abstract Objectives To assess the effects of a 9‐week yoga intervention on chronic nonspecific neck pain 12 months after completion. Design Twelve‐month follow‐up of the pooled data of both arms of a randomized, controlled trial. Setting Department of Internal and Integrative Medicine at an academic teaching hospital. Subjects Fifty‐one patients with chronic nonspecific neck pain (mean age 47.8 years; 82.4% female). Interventions A 9‐week yoga group intervention. Outcome Measures Neck pain intensity (100‐mm visual analog scale), functional disability (neck disability index), health‐related quality of life (short‐form 36 questionnaire, SF‐36), generic disability (days with restricted activities), and global improvement. Results From baseline to 12‐month follow‐up, pain intensity improved from 48.81 ± 17.71 to 32.31 ± 20.68 (P < 0.001), neck‐related disability decreased from 25.26 ± 9.02 to 19.49 ± 11.52 (P = 0.001), and bodily pain in the SF‐36 improved from 49.37 ± 12.40 to 59.26 ± 17.57 (P = 0.005). Improvements in pain intensity were predicted by weekly minutes of yoga practice during the past 4 weeks (r2 = 0.12, P = 0.028); improved neck‐related disability (r2 = 0.24, P = 0.001) and bodily pain (r2 = 0.26, P = 0.006) were predicted by regular yoga practice during the past 12 months. Generic disability did not decrease significantly. Twenty‐four patients (68.6%) rated their health as at least somewhat improved. Conclusions A 9‐week yoga intervention improved pain and neck‐related disability for at least 12 months after completion. Sustained yoga practice seems to be the most important predictor of long‐term effectiveness.